2016
DOI: 10.1007/s13105-016-0538-9
|View full text |Cite
|
Sign up to set email alerts
|

M3 cholinoreceptors alter electrical activity of rat left atrium via suppression of L-type Ca2+ current without affecting K+ conductance

Abstract: Electrophysiological effects produced by selective activation of M3 cholinoreceptors were studied in isolated left atrium preparations from rat using the standard sharp glass microelectrode technique. The stimulation of M3 receptors was obtained by application of muscarinic agonist pilocarpine (10 M) in the presence of selective M2 antagonist methoctramine (10 M). Stimulation of M3 receptors induced marked reduction of action potential duration by 14.4 ± 2.4% and 16.1 ± 2.5% of control duration measured at 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It has been accepted that M 2 R is not the only functional subtype muscarinic and nicotinic acetylcholine receptors (mAChRs) in the heart (Saternos et al, 2018). Numerous studies have reported that M 3 R plays an important role in heart diseases (Filatova et al, 2017; Xue et al, 2017). However, these studies primarily focused on cardiomyocytes and no studies have reported the expression and function of M 3 R in cardiac fibroblasts, though it has been shown that M 3 R is expressed in certain types of non-cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been accepted that M 2 R is not the only functional subtype muscarinic and nicotinic acetylcholine receptors (mAChRs) in the heart (Saternos et al, 2018). Numerous studies have reported that M 3 R plays an important role in heart diseases (Filatova et al, 2017; Xue et al, 2017). However, these studies primarily focused on cardiomyocytes and no studies have reported the expression and function of M 3 R in cardiac fibroblasts, though it has been shown that M 3 R is expressed in certain types of non-cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Present and previous studies show that expression of the M 2 mACh receptor and GIRK4 is negatively controlled by AT 1 receptor expression [6,21]. ACh-induced activation of K ACh channel could induce local hyperpolarization leading to a decrease of Ca 2+ entry through inhibition of L-type Ca 2+ channels located at the plasma membrane of atrial cardiomyoytes [31] (Fig. 8).…”
Section: Discussionmentioning
confidence: 62%
“…To induce the selective activation of M3 cholinoreceptors we have used the protocol with muscarinic agonist pilocarpine validated by several earlier studies ( Abramochkin et al, 2012 ; Wang et al, 2012 ; Filatova et al, 2017 ), although more selective and high-affine antagonists of M2 and M3 receptors were used. Muscarinic agonist pilocarpine (10 -5 M) with slight selectivity to M1 and M3 receptors was applied to the experimental chamber alone or in the presence of highly selective M2 antagonist AQ-RA 741, 10 -7 M ( Doods et al, 1991 , 1994 ; Ivanova et al, 2019 ) after prior exposure of preparations to AQ-RA 741 alone.…”
Section: Methodsmentioning
confidence: 99%
“…25 μM β-escin was added to Cs + -based pipette solution as a perforating agent, only the freshly-prepared solution with β-escin was used throughout one experimental day, but not stored further. Perforated patch technique allowed to record I CaL with minimal rundown ( Fu et al, 2003 ; Filatova et al, 2017 ). The peak current density after 10 min of continuous recording was not less than 90% of control level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation